STRATEGI PEMBELAJARAN FIQH DENGAN PROBLEM-BASED LEARNING - Marhamah Saleh (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2013)
Problem Based Learning (PBL) is a method of learning which guide the learners to solve the problem and make some reflection by using their experiences so that their cognitive skills can be developed (inquiry, communication and connection) especially in solving the problem which is meaningful, relevance and contextual. PBL is a method in contextual teaching Learning based on the theory of constructivism. The result of study showed that PBL is suitable to be applied in teaching Fiqh, and can be combined with other conventional methods to reach an optimum learning teaching. Besides, PBL is effective to ease the students’ understanding and to connect their knowledge with the reality of the problem existed in the society.